To fill in the table using the function rule, we need to substitute different values of x into the equation and solve for y. Let's consider a few values of x:
For x = 0:
y = 2(0) + 5 = 0 + 5 = 5
For x = 1:
y = 2(1) + 5 = 2 + 5 = 7
For x = -1:
y = 2(-1) + 5 = -2 + 5 = 3
For x = 2:
y = 2(2) + 5 = 4 + 5 = 9
For x = -2:
y = 2(-2) + 5 = -4 + 5 = 1
The filled table would look like this:
| x | y |
|-----|-----|
| 0 | 5 |
| 1 | 7 |
| -1 | 3 |
| 2 | 9 |
| -2 | 1 |
Y= 2x + 5. Fill in the table using this function rule
1 answer